Huzurevinde Bulunan Yaşlıların Yalnızlık Algısı ve YaşamKaliteleri Arasındaki İlişkinin İncelenmesi - (:unkn) unknown (My University, 2021)
Bu araĢtırmanın amacı yaĢlı bireylerin yalnızlık algılarının yaĢam kaliteleriyle arasındaki iliĢkiyi incelemektir. Ayrıca; huzurevindeki bireylerin YaĢlılar için YaĢam Kalitesi Ölçeği ve YaĢlılar için Yalnızlık Ölçeğinden (YĠYÖ) aldıkları puanların bazı demografik özelliklere göre (cinsiyet, yaĢ, eğitim seviyesi, kurumda kaldığı süre, kurumdan memnuniyet düzeyi) farklılaĢma durumları incelenmiĢtir. AraĢtırmanın örneklemini Ġstanbul BüyükĢehir Belediyesi Darülaceze Müdürlüğü Huzurevi‟nde yaĢayan 69‟u kadın, 127‟si erkek olmak üzere toplamda 196 yaĢlı birey oluĢturmuĢtur. Katılımcıların demografik bilgilerini belirlemek için kiĢisel bilgi formu, yalnızlık düzeylerini ölçmek için YaĢlılar için Yalnızlık Ölçeği, yaĢam kalitesini ölçmek için YaĢlılar için YaĢam Kalitesi Ölçeği uygulanmıĢtır. AraĢtırmadan elde edilen bulgular incelendiğinde; yaĢlı bireylerin yalnızlık puanları ile yaĢam kaliteleri arasında ters yönde anlamlı bir iliĢki olduğu ve yalnızlığın yaĢam kalitesini yordadığı görülmüĢtür. Ayrıca yaĢlı bireylerin yalnızlık düzeylerinin cinsiyet ve eğitim durumu değiĢkenlerine göre farklılaĢtığı ancak yaĢ, kurumda kalma süresi ve kurumdan memnuniyete göre değiĢmediği görülmüĢtür. YaĢlı bireylerin yaĢam kalitelerinin cinsiyet, eğitim durumu ve kurumdan memnuniyetlerine göre farklılaĢtığı ancak yaĢlarına ve kurumda kalma süresine göre değiĢmediği belirlenmiĢtir. Elde edilen bulgulara göre yaĢlılarla yapılabilecek çalıĢmalara dair öneriler getirilmiĢtir.

The purpose of this study is to analyze the connection between the perception of loneliness and quality of life of old people. Morever, the scores that the old people got from the Quality of Life Scale and Loneliness Scale for Elderly were analyzed based on some demographic characteristics such as gender, age, marital status, level of education, children (if any), the length of stay in retirement home, the satisfaction from the retirement home etc.. The sample of the study was performed in a retirement home (Ġstanbul BüyükĢehir Belediyesi Darülaceze Müdürlüğü) with 69 female and 127 male persons. The demographic data of the participants was obtained from the Personal Information Form, where Loneliness Scale for Elderly for the Loneliness score and Quality of Life Scale for Elder People for the life quality score. As a result of the analyses; a meaningful negative connection was found out between the level of loneliness and quality of life. A distinct connection was noticed between the loneliness score and the level of education. Also loneliness predicts quality of life. In addition, it was observed that the loneliness levels of elder people differed according to the variables of gender and educational status, but did not change according to age, length of stay in the retirement home and satisfaction with the retirement home. It has been determined that the quality of life of older individuals differs according to their gender, educational status and satisfaction with the retirement home, but does not change according to their age and length of stay in the retirement home. Based on the findings, suggestions were made for studies that could be done with the elderly.
Investigation of the Relationship between Perception of Loneliness and Quality of Life of the Elderly in Nursing Home